2021
DOI: 10.1080/15476286.2020.1871217
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the expression and functionality of the rsm sRNAs in Pseudomonas syringae pv. tomato DC3000

Abstract: The Gac-rsm pathway is a global regulatory network that governs mayor lifestyle and metabolic changes in gamma-proteobacteria. In a previous study, we uncovered the role of CsrA proteins promoting growth and repressing motility, alginate production and virulence in the model phytopathogen Pseudomonas syringae pv. tomato (Pto) DC3000. Here, we focus on the expression and regulation of the rsm regulatory sRNAs, since Pto DC3000 exceptionally has seven variants (rsmX1-5, rsmY and rsmZ). The presented results offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 98 publications
(209 reference statements)
1
12
0
Order By: Relevance
“…Another conserved feature is the induction of the expression and/or activity of GacA/UvrY by the CsrA/Rsm proteins. This usually results in enhanced Csr/Rsm RNA expression (Gudapaty et al ., 2001; Suzuki et al ., 2002; Kay et al ., 2005; Fortune et al ., 2006; Humair et al ., 2010; Camacho et al ., 2015; Butz et al ., 2019; Ferreiro et al ., 2021), generating a negative feedback loop that reduces the response times to the stimuli (Adamson and Lim, 2013). Likewise, the CsrA/Rsm proteins would also affect the expression of other genes directly controlled by GacA/UvrY, if any.…”
Section: Essential Features Of the Gac‐rsm Pathwaymentioning
confidence: 99%
See 4 more Smart Citations
“…Another conserved feature is the induction of the expression and/or activity of GacA/UvrY by the CsrA/Rsm proteins. This usually results in enhanced Csr/Rsm RNA expression (Gudapaty et al ., 2001; Suzuki et al ., 2002; Kay et al ., 2005; Fortune et al ., 2006; Humair et al ., 2010; Camacho et al ., 2015; Butz et al ., 2019; Ferreiro et al ., 2021), generating a negative feedback loop that reduces the response times to the stimuli (Adamson and Lim, 2013). Likewise, the CsrA/Rsm proteins would also affect the expression of other genes directly controlled by GacA/UvrY, if any.…”
Section: Essential Features Of the Gac‐rsm Pathwaymentioning
confidence: 99%
“…Interestingly, P. syringae pv. tomato (Pto) DC3000 has seven Rsm RNAs (RsmX1‐5, RsmY and RsmZ) and the alignment of their promoter regions revealed that all of them have a likely GacA‐box (Moll et al ., 2010), but the motifs exhibit particularities which makes them to be differentially regulated by this protein (Ferreiro et al ., 2021). As it was mentioned before, the Rsm RNA levels are also controlled by other regulators, such as HptB and MvaT, which downregulate RsmZ expression in P. aeruginosa (Brencic et al ., 2009; Jean‐Pierre et al ., 2016), IHF, PsrA and AlgR, that promote the transcription of RsmZ in P. protegens CHA0 (Humair et al ., 2010; Li et al ., 2017), or a hairpin structure, which may be the target of an unknown transcriptional factor and is essential for full RsmZ expression in P. brassicacearum NFM421 (Lalaouna et al ., 2012a).…”
Section: Special Features Of the Gac‐rsm Pathway In Pseudomonas Assoc...mentioning
confidence: 99%
See 3 more Smart Citations